Parties of Power: Understanding the Significance of Congress and BJP in Shaping Indian Democracy - Younis Ahmad Sheikh; Imran Majeed (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2023)
The Congress Party has a long history linked to India’s independence movement and is associated with a secular and socialist ideology. The BJP, founded in 1980, is associated with Hindu nationalism and has become increasingly influential in recent years. The parties have significant differences in policies and agendas, including economic and social issues. Understanding the role of political parties in Indian democracy is essential for gaining a deeper understanding of the country’s political landscape and the challenges it faces. This article compares the Congress Party and the Bharatiya Janata Party (BJP), two major political parties in India, and examines their historical backgrounds, ideologies, and election strategies. The role of political parties in Indian democracy is discussed, along with the challenges faced by both parties in recent elections. The article concludes by highlighting the significance of political parties in Indian democracy and discussing the future prospects of the Congress Party and the BJP.